Analyzing factors that affect reading habits among Generation Y patronages at MPH Giant Stadium Shah Alam / Syafiqah Amira Abdullah - Abdullah, Syafiqah Amira (2015)
Reading habit is a crucial aspect to create literate society in this world. It helps to develop proper thinking skills and methods and creating new ideas. Reading habit in Malaysia is still at the low level. This shows that they are not interested in making reading as their habit. This research is designed to study on factors affecting reading habits among Generation Y patronages at MPH in preparing themselves as a reading society. The research consists of four factors which are types of reading material, media, culture and peer influence. The objectives of this research aim to study the level of readiness of reading habit among Generation Y in becoming a reading society, to analyze the relationship between types of reading material, media, culture, peer influences towards reading habit, to identify which factor is the most influencing factor on Generation Y reading habit, and to recommend ways to cultivate reading habits among Generation Y. Using convenience sampling, 100 visitors were selected and questionnaires were distributed to 100 respondents which is Generation Y patronages at MPH Giant Stadium Shah Alam. Results of the study revealed that culture is the most important factors in affecting reading habits among Generation Y.